Revisión bibliográfica de los protocolos de manejo de microorganismos biocontroladores (Beauveria bassiana) en su captura, aislamiento y propagación, Latacunga, Salache – CEYPSA, 2020-2021. - Morales Meneses, Daniel Alexis (2021)
Beauveria bassiana is an entomopathogenic fungus that develops naturally in soils and surfaces around the world being the main cause of the disease called white muscardine, behaving as a parasite for several species of arthropods (Aziz & Lárez, 2016). In Ecuador and the world, despite the existence of information, there has not been a compilation or database that focuses on methods to capture, isolate and propagate this entomopathogenic fungus. Thus, the objective of this work is to carry out a bibliographic review of the protocols for the capture, isolation and propagation of this fungus. The methodology used in the research is based on the search of 150 articles, where the selection of information was based on the determination of the subject of study, specification of topics, bibliographic management, debugging of the database and systematization, resulting in 90 documents verified between journal articles, theses and reports within a timeline of 10 years ago. In relation to the capture methods found in the research there are 3 ways by which this fungus can be obtained, according to Mondal & Baksi (2018) it can be collected from soil samples, while Castillo (2012); Sayed (2020) state that it can also be by means of insects or samples of plant material that are infected by the fungus. On the other hand, the isolation methods most research refers to the use of culture media (PDA, ADS, AMC), silica gel crystals, each of these formed by different compositions (Choquetarqui Daniel et al., 2011; Lucero et al., 2004; Merino, 2017; Mondal & Baksi, 2018). Methods that give way to the propagation of the fungus where the use of organic substrates (wheat grains, rice), combination of culture media, serve to propagate this entomopathogenic microorganism (Alvarado et al., 2013; Choquetarqui Daniel et al., 2011; Gómez et al., 2014; Lucero et al., 2004).